Study on the Association Network of Tuberculosis Lesions in Adult Extrapulmonary Tuberculosis in China: A Large-Scale Multicenter Observational Study - Jiajia Yu; Yunqing Chang; Chen Liang; Shengsheng Liu; Liang Li; Jian Du; Youcai Li; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: The present study revealed the occurrence of concurrent EPTB types and analyzed the association network and rules among adult EPTB for the first time in a large sample population. Clinicians should be alert to the incidence of concurrent EPTB and that these patients require administration of customized treatment regimens in order to achieve the best outcomes.